2015
DOI: 10.1189/jlb.4a0315-115rr
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lung infection–induced TCRγδ T cell phenotypes by CyTOF mass cytometry

Abstract: T cell receptor γδ cells are known to be the primary effector T cells involved in the response to bacterial infections, yet their phenotypic characteristics are not as well established as other T cell subsets. In this study, we used cytometry by time-of-flight mass cytometry to better characterize the phenotypic response of T cell receptor γδ cells to Streptococcus pneumoniae lung infection. Mice were infected, and cells from lung washouts, spleen, and lymph nodes were stained to detect cell-surface, intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Other studies showed that increased γδ T cells in the lungs after S. pneumoniae infection expressed high levels of IFN‐ γ and IL‐17A. Activated γδ T cells uniquely co‐express Gr‐1, CD14 and CD274 (PD‐L1), and Gr‐1 expression patterns on lung γδ T cells provide a marker to differentiate IFN‐ γ (Gr‐1 + )‐ and IL‐17A (Gr‐1 − ) ‐producing subsets . It was also found that the resolution of S. pneumoniae ‐induced lung inflammation was associated with a > 30‐fold increase in γδ T‐cell number, which decreased the number of pulmonary dendritic cells and alveolar macrophages …”
Section: Involvement Of γδ T Cells In Lung Diseasesmentioning
confidence: 99%
“…Other studies showed that increased γδ T cells in the lungs after S. pneumoniae infection expressed high levels of IFN‐ γ and IL‐17A. Activated γδ T cells uniquely co‐express Gr‐1, CD14 and CD274 (PD‐L1), and Gr‐1 expression patterns on lung γδ T cells provide a marker to differentiate IFN‐ γ (Gr‐1 + )‐ and IL‐17A (Gr‐1 − ) ‐producing subsets . It was also found that the resolution of S. pneumoniae ‐induced lung inflammation was associated with a > 30‐fold increase in γδ T‐cell number, which decreased the number of pulmonary dendritic cells and alveolar macrophages …”
Section: Involvement Of γδ T Cells In Lung Diseasesmentioning
confidence: 99%
“…cannula was inserted into trachea via neck incision. Lungs were lavaged three times with 1 mL of phosphate buffered saline, fluid collected, and cell suspension obtained, as previously described 45 . Cells were cryopreserved as described above for subsequent CyTOF antibody staining.…”
Section: Isolation Of Immune Cells From Whole Lung and Bronchoalveolamentioning
confidence: 99%
“…Advantages of this platform offers include tracking kinetics of cellular trafficking and studying interactions between many phenotypically and diverse immune cell subsets . For example, a recent study using CyTOF found that identification of a unique γδ T cell subset expressing Ly‐6G myeloid differentiation antigen enabled distinguishing between IL‐17A‐ and IFN‐γ‐producing cells in the lungs of S. pneumoniae infected mice .…”
Section: Protective Role Of Th17 Responses During Infection With Strementioning
confidence: 99%